Differential influence of maternal and fetal pregnancy factors on the in-vitro induction of human regulatory T cells: a preliminary study (Swiss Medical Weekly, 2015)
PROBLEM: Given the important role of regulatory T cells (Treg) for successful pregnancy, the ability of soluble maternal and fetal pregnancy factors to induce human Treg was investigated. METHOD OF STUDY: Peripheral blood mononuclear cells (PBMCs) or isolated CD4+CD25‒ cells were cultured in the presence of pooled second or third trimester pregnancy sera, steroid hormones or supernatants from placental explants, and the numbers and function of induced CD4+CD25+FOXP3+ Treg were analysed. RESULTS: Third trimester pregnancy sera and supernatants of early placental explants, but not sex steroid hormones, induced an increase of Tregs from PBMCs. Early placental supernatant containing high levels of tumour necrosis factor-α, interferon-γ, interleukins -1, -6 and -17, soluble human leucocyte antigen-G, and transforming growth factor-β1, increased the proportion of Treg most effectively and was able to induce interleukin-10-secreting-Treg from CD4+CD25‒cells. CONCLUSIONS: Compared with circulating maternal factors, placental- and fetal-derived factors appear to exert a more powerful effect on numerical changes of Treg, thereby supporting fetomaternal tolerance during human pregnancy.